2021
DOI: 10.1177/1745691621989243
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Behavioral Predictors of Vaccine Efficacy: Considerations for COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine candidates are being evaluated, with the goal of conferring immunity on the highest percentage of people who receive the vaccine as possible. It is noteworthy that vaccine efficacy depends not only on the vaccine but also on characteristics of the vaccinated. Over the past 30 years, a series of studies has documented the impact of psychological factors on the immune system’s vaccine response. Robust evidence has demonstrated that stress, depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(135 citation statements)
references
References 104 publications
2
114
0
2
Order By: Relevance
“…More emotionally compelling content should be included in COVID-19 vaccine promotion, accompanying by strengthen the trust and credibility of government organizations and experts. Furthermore, psychological factors like stress and depression were believed to impair the immune system's response and exacerbate side effects to vaccines, which could be aggravated by the COVID-19 pandemic ( Madison et al, 2021 ). Early evidence has suggested that psychological interventions may improve the antibody response to vaccines ( Vedhara et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…More emotionally compelling content should be included in COVID-19 vaccine promotion, accompanying by strengthen the trust and credibility of government organizations and experts. Furthermore, psychological factors like stress and depression were believed to impair the immune system's response and exacerbate side effects to vaccines, which could be aggravated by the COVID-19 pandemic ( Madison et al, 2021 ). Early evidence has suggested that psychological interventions may improve the antibody response to vaccines ( Vedhara et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These two convergent pathways synergistically contribute to mitigate the clinical impact of SARS-CoV-2, as attested by recent evidence reviewed by Abdool Karim and de Oliveira [ 10 ], showing that mRNA-LNPs may display 94–95% efficiency in preventing SARS-CoV-2 infection and 90–100% efficacy in averting severe COVID-19 illness. Nonetheless, concerns have been expressed that the immune response after administration of these mRNA-LNPs may be characterized by high inter-individual variation, with some people developing higher titers of neutralizing antibodies compared to others who may only have a “mild” and thus less efficient response [ 11 , 12 , 13 ]. Therefore, this retrospective observational study was aimed to monitor the anti-SARS-CoV-2 RBD total antibodies response in a large population of healthcare workers, both SARS-CoV-2 seropositive and seronegative, undergoing voluntary mRNA vaccine administration.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to reduce the spread of SARS-CoV-2 by social distancing are associated with reduced COVID-19 disease rates per unit time (9)(10)(11)(12)(13)(14) but also incur substantial psychological, social, cultural, medical, and economic costs (14)(15)(16)(17)(18). Most cost-benefit analyses of social distancing policies overlook the fact that social contact is also an essential resource for optimal immune function (19)(20)(21). As such, extreme social distancing measures such as extended "stay at home" or "shelter in place" (SIP) orders may paradoxically increase vulnerability to viral infection (conditional on viral exposure) even as they reduce the risk of viral exposure.…”
mentioning
confidence: 99%